HUKUM ADAT DALAM PERKEMBANGAN: PARADIGMA SENTRALISME HUKUM DAN PARADIGMA PLURALISME HUKUM - Rizka Fakhrurozi; Erwin Syahrudin (The Juris, 2022)
The paradigm of understanding customary law and its development must be placed in a large space, by examining extensively: a) Studies that no longer look at the legal system of a country in the form of state law, but also customary law, religious law and customary law; b) Understanding of law (adat) not only understands customary law in traditional communities- rural communities, but also the laws that apply in certain environmental communities (hybrid law or unnamed law); c) Understanding the phenomenon of trans-national law as the law made by multilateral organizations, then there is an interdependence relationship between international law, national law and local law. With a holistic and integrative understanding, the development and position of customary law will be adequately understood. Positively means that customary law is seen as law that comes from the thoughts and ideals of the people. Negatively, customary law is seen from the outside, from its relationship with other laws, both strengthening and weakening and the interaction of state political developments. Positive legal developments mean that customary law will be recognized in society in doctrine, legislation, in jurisprudence and in everyday life. On the other hand, the negative development is how customary law is sidelined and displaced or completely invalidated by their existence positive law represented by the State both in legislation and in court decisions.